Efecto del número de racimos por planta sobre el rendimiento de tomate (Solanum lycopersicum L.) - Quintana Baquero, Rafael Alberto; Balaguera López, Helber Enrique; Álvarez Herrera, Javier Giovanni; Cárdenas Hernández, Julián F.; Pinzón, Helberth Hernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2012)
.